Metastatic Carcinoma Occurring in a Gastric Hyperplastic Polyp Mimicking Primary Gastric Cancer: The First Reported Case - Gabriel M. Groisman; Roman Depsames; Baruch Ovadia; Alona Meir (Case Reports in Pathology)
Hyperplastic polyps of the stomach are regarded as benign. However, in rare cases they may contain incipient primary carcinomas. To our knowledge, breast carcinoma metastatic to a gastric hyperplastic polyp has not yet been reported. We describe the case of a 69-year-old woman to whom a gastric polyp was endoscopically excised. The patient had previously undergone a right mastectomy for mixed, invasive ductal and lobular carcinoma 5 years earlier. Histological sections from the gastric lesion showed typical features of hyperplastic polyp with foci of poorly differentiated adenocarcinoma including signet ring cells infiltrating the lamina propria. The histologic findings were consistent with a primary gastric cancer. However, the carcinoma cells were immunopositive for estrogen and progesterone receptors and GATA3 and negative for CDX2, Hep Par 1, and MUC5AC. E-cadherin showed membranous reactivity in some of the carcinoma cells while in others it was negative. Accordingly, metastatic mixed, lobular and ductal breast carcinoma was diagnosed. We conclude that metastatic adenocarcinoma mimicking primary gastric cancer can be rarely encountered in hyperplastic gastric polyps.